NORMATIF-TEOLOGIS SEBAGAI PENDEKATAN STUDI ISLAM: SYTEMIC LITERATURE REVIEW - Aslinda, Aslinda; Ritonga, Mahyudin (Universitas Muhammadiyah Tangerang, 2024)
Various approaches in Islamic studies have provided extensive knowledge and studies related to the field of Islamic science, but the many approaches do not necessarily close the space for academics to explore more deeply and even criticise the existing approaches, this is because there is always room for argumentation between fellow academics. Therefore, this study is focused on investigating and finding a normative-theological approach to Islamic studies. The focus of the study of this article is the definition of the normative-theological approach, its scope, as well as the scope of problems and areas. Not only exploring the normative-theological aspects (doctrinal and doctrinal), this research also describes the relationship between normative-theological studies in Islamic studies and other sciences (knowledge) so that studies can be enriched, updated, and relevant to the times and beneficial for life and civilization. The method used in this research is qualitative with the type of library research, the data is analyzed with comparative techniques, namely comparing several opinions related to the research content. The results of the analysis can be concluded that a doctrine and teaching will truly function and exist if it continues to dialogue and respond to the dynamics of the times that are constantly moving, changing, even revolutionary. The importance of normative-theological studies in Islamic studies to dialogue and be enriched with existing science and will continue to develop in accordance with the movements and dynamics of the times. This research provides an important contribution that Islamic studies have a normative-theological side that must be maintained, but must also be enriched with other scientific perspectives and dialogue with the movements of the times and the problems of mankind and life so that a religious teaching (in this case Islam) can be useful in history and civilization.